FAKTOR-FAKTOR MOTIVASI SISWA SMK NEGERI 4 DENPASAR MENGIKUTI STUDY TOUR KE PULAU JAWA - Pande Putu Juniarta; Made Antara; I Wayan Suardana (Magister Tourism Study, Faculty of Tourism, Udayana University, 2018)
Study tour is a school program that aims to learn the latest phenomenon of a visited tourism destination. This activity provides students with immediate experience related to situation of tourism attraction not obtainable at school. This study analyzes about the level of student motivation and motivation factors of students of SMK Negeri 4 Denpasar to follow a study tour to Java. The data obtained through lling out a questionnaire. The data were analyzed using con rmatory factor analysis. The results shows that the students motivation level following a study tour is very high and there are four factors of student motivation to follow the study tour namely physical, cultural, social, and fantasy motivation. The dominant factor that in uenced the student to take part in the study tour is the cultural motivation factor. Based on the analysis, all the variable can explain four factors which motivate students of SMK 4 Denpasar to take part in the study tour to Java.